South Asia and the Great Powers : International Relations and Regional Security - Edited by Rynning, Sten (London I. B. Tauris, 2017)
La quatrième de couverture porte :"In the wake of the international combat mission in the Afghanistan, South Asia's security is becoming a fator of increasing importance both to local and more distant great powers : Pakistan, India, Iran, China, and the US. Where the implications of war and peace are open to question, the possibility of change depends more on politics than economics. This book asks whether the region's great powers can overcome opposing interests and commit to political restraint. The concept of regional security is based on great power support for regional order. However, there are many pitfalls to consider: notably, the politics of contested nationalisms; the Asia-Pacific rivalry of China and the US; and India's inclinations to function - or be seen - as a benevolent hegemon for the region. Yet there are signs of renewed determination to move the region in new directions. While China's Silk Road projects are long-term regional investments that hinge on regional stability, the US is attempting to fashion new partnerships and India strives to reconcile regional differences to promote a peaceful environment. This book, as it sets out the emerging agendas of the great powers and local powers, makes a significant contribution to a better understanding of the international relations and diplomatic politics of South Asia."
Include Index
Keywords: South Asia -- Diplomatic relations -- National security